Analysis Perovskite Material Absorber Based on Nd0.6Sr0.4MnxFe1/2(1-x)Ti1/2(1-x)O3 (x = 0, 0.1, 0.2) by Sol-Gel Method - Fajar Arif Kurniawan; Sitti Ahmiatri Saptari; Arif Tjahjono; Deni Shidqi Khaerudini (Universitas Sebelas Maret, 2022)
The purposes of this research is to synthesis Nd0.6Sr0.4MnxFe1/2(1-x)Ti1/2(1-x)O3 (x = 0. 0.1, 0.2) materials as electromagnetic wave absorber using the sol-gel method. Materials characterized using X-Ray Diffraction (XRD) to determine the phase formed and Vector Network Analyzer (VNA) to determine the ability or strength of absorption of electromagnetic waves. The result of XRD material has a structure orthorhombic with space group P b n m (62-3), the substitution of Mn+3 ions on Fe+3 ions and Ti+4 ions causes a phase change of the material from when x =0 in the absence of Mn+3 ions 2 phases are formed, while when Mn+3 is substituted 1 phase is formed. The result of VNA with a frequency range of 8 – 12 GHz shows that the material has the ability to absorb electromagnetic waves up to 98,22% at a frequency of 9,5 GHz when x = 0.2. Thus, the material synthesis Nd0.6Sr0.4MnxFe1/2(1-x)Ti1/2(1-x)O3 has been successfully synthesized and has the ability to absorb electromagnetic waves.